MENTAL SELF-REGULATION AND IMPLEMENTATION OF PREPAREDNESS IN COMPETITIONS AMONG ATHLETES WITH DIFFERENT LEVELS OF HARDINESS - Lovyagina A.E.; Ilyina N.L.; Lukina S.M.; Shindrikova E.V. (Theory and Practice of Physical Culture, 2023)
Objective of the study was a comparative analysis of the indicators of mental self–regulation and physical fitness performance at the competitions among athletes with different hardinesslevel. Methods and structure of the study. A psychodiagnostic examination of athletes (men and women) of different sports was carried out according to the hardiness test and questionnaire for the diagnosis of indicators of mental self-regulation in difficult situations of competition. Results and conclusions. Differences in the level of control among athletes of different sexes and different sports were revealed. It has been established that in connection with the severity of involvement, control and the general level of resilience, athletes have different processes of mental self-regulation in competition conditions. Differences were found in the implementation of readiness (training) in athletes with different levels of control and risk taking.